KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN KERJA GURU DI UPT SMA NEGERI 12 WAJO KECAMATAN KEERA - Asrijal Asrijal; Sumarni Sumarni; Hasriani Hasriani (STKIP Pesisir Selatan, 2026)
This study aims to analyze the application of democratic leadership by school principals in improving teacher work discipline at UPT SMA Negeri 12 Wajo, Keera District. The main issue raised is how democratic leadership style is applied and how it impacts the improvement of teacher work discipline. The method used is a qualitative approach with descriptive research, where data is collected through observation, interviews, and documentation studies. Research informants include the principal, vice principal for student affairs, and several subject teachers. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing and verification. The results of the study show that the head of the Wajo 12 Public High School UPT consistently applies the principles of democratic leadership through the involvement of teachers in decision-making, appreciation of individual potential, and active collaboration among school members. The application of this leadership style has had a real impact on improving teacher work discipline, as seen in increased punctuality, compliance with rules, and professional responsibility in carrying out tasks. These findings contribute to the development of participatory leadership models in secondary education environments to strengthen a collaborative and professional work culture.